Endoscopic Closure for EUS and ERCP Related Duodenal Perforation by Endoclips - Yaping Liu; Dong Wang; Zhaoshen Li (Gastroenterology Research and Practice)
Objective. To investigate the therapeutic safety, feasibility, and efficacy of endoclips for closing the endoscopic ultrasound (EUS) and endoscopic retrograde cholangiopancreatography (ERCP) related duodenal perforation in a retrospective study from a single center. Methods. Patients who developed EUS and ERCP related duodenal perforation between January 2012 and January 2015 were included in the study. All the cases underwent endoscopic closure by endoclips, and the efficacy, feasibility, and safety of this technique were evaluated. Results. During the study period, a total of 17,406 patients were treated by EUS and/or ERCP. EUS and ERCP related duodenal perforation occurred in 9 cases (0.05%): 2 males and 7 females. The mean age was 69 years (range: 59–79 years). The success rate of endoscopic closure by endoclips was 100%. The mean procedure time was 45±12.5 min. The mean number of endoclips placed for the closure of the duodenal perforation was 7±3.2. All the patients recovered completely without any severe complications. Conclusion. The endoscopic closure by using endoclips is recommended as the first-line treatment for duodenal perforation associated with EUS and ERCP.